Pharmacological target therapy of neuropathic pain and patient-reported outcomes in patients with chronic low back pain in Korea: Results from the NLBP Outcomes Research. Issue 35 (August 2018) - Hong, Jae Taek; Kim, Jin-Hwan; Kim, Keun-Su; Lee, Chong-Suh; Shin, Hyun-Chul; Kim, Woo-Kyung; Kim, Joo-Han; Lee, Jung-Kil; Kim, In-Soo; Ha, Yoon; Im, Soo-Bin; Kim, Sang Woo; et al.
Abstract : Abstract: A number of studies have demonstrated an association of neuropathic pain and chronic low back pain (CLBP), but the outcome difference in each medical management is poorly understood. This study is aimed to investigate treatment patterns of neuropathic pain in CLBP patients and to explore patient-reported outcomes (PROs) including quality of life (QoL) and functional disability by treatment patterns. Data were extracted from the neuropathic low back pain (NLBP) outcomes research. It was a multicenter and cross-sectional study in which 1200 patients were enrolled at 27 general hospitals, from 2014 to 2015. Of total, 478 patients classified as neuropathic pain were used for this subgroup analysis. The patients were divided into 2 groups according to treatment patterns (with vs. without the targeted therapy [TT] of neuropathic pain). Demographic and clinical features were collected by chart reviews and PROs were measured by patient's survey. QoL was assessed by EuroQoL 5-dimension (EQ-5D) questionnaire. Functional disability was measured by the Quebec Back Pain Disability Scale (QBPDS). Multiple linear regression analyses were conducted to compare the PROs between TT group and non-targeted therapy (nTT) group. Among the NLBP patients (mean age 63years, female 62%), EQ-5D index, EuroQoL-Visual Analog Scale (EQ-VAS), and QBPDS Scores (mean ± standard deviation) were 0.40 ± 0.28, 54.98 ± 19.98, and 46.03 ± 21.24, respectively. Only 142 (29.7%) patients had pharmacological TT of neuropathic pain. Univariate analyses revealed no significant mean differences between TT group and nTT group in the EQ-5D index (0.41 ± 0.27 and 0.39 ± 0.28), EQ-VAS (56.43 ± 18.17 and 54.37 ± 20.69), and QBPDS (45.31 ± 21.32 and 46.31 ± 21.24). After adjustment with covariates, TT group had higher scores of EQ-5D index (β = 0.07; P  < 0.01) and EQ-VAS (β = 4.59; P  < 0.05) than the nTT group. The TT group's QBPDS score was lower than the nTT group, although its statistical significance still has not been reached (β = −4.13; P  = 0.07). We found that considerable proportion of the NLBP patients remains untreated or undertreated. Although TT group had significantly better QoL than nTT group, only 29.7% of NLBP patients had pharmacological TT. Therefore, clinicians should consider using TT for better QoL of neuropathic pain patients.